Ni/MnO2 - newspaper as flexible and lightweight supercapacitor - Siti Liyana Sapuan (2018)
A rise in demand for flexible and wearable electronic devices has spurred the development of increasingly miniaturized, ultrathin, flexible and highly efficient energy storage components. Unlike conventional modes of energy storage, flexible storage devices require not only great stability, reliability and long cycle life but also to have excellent electrochemical performance as well as deformable mechanical properties for energy storage in flexible wearables. Among these energy storage devices, flexible supercapacitors, also known as electrochemical capacitors or ultracapacitors, gained the attention of the research community due to a series of advantages such as their fast charge-discharge rates, higher power density, larger energy storage capacity, lower cost and longer cycle life. Additionally, flexible supercapacitors are safe, reliable, lightweight, highly commercialized and are more environmental-friendly to manufacture.